Whole Genome Re-sequencing Reveals Natural Variation and Adaptive Evolution of Phytophthora sojae - Zhang, Xiong; Liu, Bo; Zou, Fen; Shen, Danyu; Yin, Zhiyuan; Wang, Rongbo; He, Feng; Wang, Yuanchao; Tyler, Brett M.; Fan, Wei; Qian, Wanqiang; Dou, Daolong (Frontiers in Microbiology, 2019)
Due to the monocultural basis of agricultural crops, mutated plant microbes with increased pathogenicity can easily spread in the field and lead to serious yield losses. As a major threat to a wide range of crop plants, oomycete pathogens continuously undergo adaptive evolution to overcome plant defense barriers. However, the genetic basis of their evolution at the molecular level remains largely unknown. Here, we investigated the nature of variation and the population genomics of the soybean pathogen Phytophthora sojae by high-throughput genome re-sequencing. Genomic variation analysis revealed uneven “two-speed” evolutionary pattern with genes in gene-sparse regions (GSRs) showing higher rates of structural polymorphisms and positive selection. GSRs are enriched in effector genes and transposase-related genes. Our results also suggested that the NADH oxidase and MIP transporter gene families undergo rapid and diversifying selection. Furthermore, we demonstrated that P. sojae isolates possess varying numbers of RxLR effectors with diverse sequences, totaling 471 members. Among them, 42 core RxLR effectors are assumed to be indispensable for infection. Finally, we observed that Avr genes exhibit abundant sequence variation in P. sojae isolates. Several novel variants lead to the evading of host resistance, including a complete deletion in Avr3c and amino acid mutations in Avr1a. Taken together, our results provide an adaptive landscape of P. sojae at single-nucleotide resolution, as well as resources for further studies of resistance breeding and disease prevention against this important plant pathogen.